FOOT SELF-CARE PADA PENYANDANG DIABETES MELLITUS (DM): PILOT STUDY DI SEMARANG - Kusumaningrum, Niken Safitri Dyan; Ashari, Ainur Muhti (Universitas Islam Negeri Alauddin Makassar, 2020)
Diabetes Mellitus is chronic metabolic disease that has the characteristics hyperglikemia due to insulin deficiency and lead to diabetic foot ulcers. That complications can be prevented by performing foot self-care. The purpose of this study was to identify foot self-care in persons with diabetes mellitus in Puskesmas Rowosari Semarang. This study was a quantitative research with cross sectional approach. The sampling technique used was consecutive sampling. Diabetic Foot Self-care Questionnaire University of Malaga was used to gather the data from diabetic. Analysis of the data used were univariate which produces tables. A total of 112 diabetic participated in the study. The majority patient participated in this study were they who age range 41-60 (69,6%), female (78,6%), did not have the experience to get education (50%), and suffering from diabetes <10 years(80,4%). The result of this study showed that 52.7% of diabetic have a good category on foot self care. In conclusion, more diabetic have good foot self-care. Therefore, it is needed to give more information for patients with diabetes in order to apply the foot self-care especially the examination of the feet, using lotion, socks, and the way to get the feet warm.